Community Empowerment for Strengthening the Local Economy Based on Cultural Heritage in Kampung Tudong, Pontianak City - Fatimah, Siti; Abdi, Egy; Meisari, Winda Chelsea (Journal of Indonesian Tourism and Policy Studies, 2025)
Kampung Tudong, located in Bansir Laut Subdistrict Pontianak City represents a local community that has successfully revitalized its cultural heritage through a traditional product called Tudong (a protective cover) made from mengkuang leaves that has existed since 1915. This product not only serves a functional purpose for the local community but also symbolizes cultural identity and has become a driver of the local economy across generations. The establishment of Kampung Tudong was driven by local residents’ concern for social and economic conditions and their independent initiative to build a craftsman village for Tudong production. This study employs a qualitative approach using a case study method. Data collection techniques included observation, interviews, and literature review. The findings reveal that community empowerment is carried out through the cultural preservation of Tudong production, community involvement in handicraft training, and the official recognition of Kampung Tudong as a cultural tourism destination by the Pontianak City Government through the Office of Youth, Sports, and Tourism. The implications of this study show that culture-based empowerment can strengthen the local economy while reinforcing community identity and solidarity. This model can be replicated in other regions through a participatory approach and cross-sectoral policy support.